2019
DOI: 10.1371/journal.pone.0222394
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome diversity is associated with sleep physiology in humans

Abstract: The human gut microbiome can influence health through the brain-gut-microbiome axis. Growing evidence suggests that the gut microbiome can influence sleep quality. Previous studies that have examined sleep deprivation and the human gut microbiome have yielded conflicting results. A recent study found that sleep deprivation leads to changes in gut microbiome composition while a different study found that sleep deprivation does not lead to changes in gut microbiome. Accordingly, the relationship between sleep ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
144
1
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(206 citation statements)
references
References 81 publications
(92 reference statements)
7
144
1
12
Order By: Relevance
“…As we have discussed in a previous review [1], food sources encouraged by a Mediterranean diet pattern, including fruits and vegetables, are often rich sources of fiber and other nutrients that can have beneficial effects on the microbial composition of the gut, such as a lower ratio of Firmicutes to Bacteroidetes [1,45]. In turn, markers of healthy composition of gut flora have been linked with better sleep [46]. However, physiological mechanisms underlying the aMed diet-sleep quality association require further investigation, possibly using clinical investigations that evaluate the effect of an aMed diet intervention on sleep quality and corresponding changes in microbial composition or circulating melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…As we have discussed in a previous review [1], food sources encouraged by a Mediterranean diet pattern, including fruits and vegetables, are often rich sources of fiber and other nutrients that can have beneficial effects on the microbial composition of the gut, such as a lower ratio of Firmicutes to Bacteroidetes [1,45]. In turn, markers of healthy composition of gut flora have been linked with better sleep [46]. However, physiological mechanisms underlying the aMed diet-sleep quality association require further investigation, possibly using clinical investigations that evaluate the effect of an aMed diet intervention on sleep quality and corresponding changes in microbial composition or circulating melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…They found that total microbiome diversity was positively correlated with increased sleep efficiency and total sleep time along with positive correlations between total microbiome diversity and interleukin-6. Their analysis of the microbiome composition revealed that phyla richness of Bacteroidetes and Firmicutes were positively correlated with sleep efficiency and several taxa like Lachnospiraceae, Corynebacterium and Blautia were negatively correlated with sleep measures [82]. These quantified sleep measures differ clearly from the self rating measures described in the reviewed papers in patients with psychiatric diseases and clarify the need of objective measures in patients with psychiatric diseases.…”
Section: Gut Microbiome Diversity Is Associated With Sleep Physiologymentioning
confidence: 93%
“…But the assessment of metabolic function is only based on PICRUSt function prediction. Smith et al also con rmed the association between gut microbiota diversity and sleep physiology 22 . In addition, they found that positive correlations between total microbiome diversity and IL-6.…”
Section: Discussionmentioning
confidence: 97%